Pharmacologic Calcitriol Inhibits Osteoclast Lineage Commitment via the BMP‐Smad1 and IκB‐NF‐κB Pathways. (9th May 2017) - Li, Anna; Cong, Qian; Xia, Xuechun; Leong, Wai Fook; Yeh, James; Miao, Dengshun; Mishina, Yuji; Liu, Huijuan; Li, Baojie
ABSTRACT: Vitamin D is involved in a range of physiological processes and its active form and analogs have been used to treat diseases such as osteoporosis. Yet how vitamin D executes its function remains unsolved. Here we show that the active form of vitamin D calcitriol increases the peak bone mass in mice by inhibiting osteoclastogenesis and bone resorption. Although calcitriol modestly promoted osteoclast maturation, it strongly inhibited osteoclast lineage commitment from its progenitor monocyte by increasing Smad1 transcription via the vitamin D receptor and enhancing BMP‐Smad1 activation, which in turn led to increased IκBα expression and decreased NF‐κB activation and NFATc1 expression, with IκBα being a Smad1 target gene. Inhibition of BMP type I receptor or ablation of Bmpr1a in monocytes alleviated the inhibitory effects of calcitriol on osteoclast commitment, bone resorption, and bone mass augmentation. These findings uncover crosstalk between the BMP‐Smad1 and RANKL‐NF‐κB pathways during osteoclastogenesis that underlies the action of active vitamin D on bone health. © 2017 American Society for Bone and Mineral Research.